GROUP INVESTIGATIONS DAN TEAM GAMES TOURNAMENT UNTUK IPS DI SMK - Enden Sopa Sopiyana; R Gunawan Sudarmanto; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
The focus of the research is to examine the difference between GI and TGT learning model towards students’ achievement. The problem analyzed in the research is to know the difference between, the learning models and students’ early ability towards their achievement, GI and TGT learning model towards the students’ early achievement with high scores in social studies, GI and TGT learning model towards the students’ early achievement with average scores in social studies, GI and TGT learning model towards the students’ early achievement with low scores in social studies, the interaction between the use of learning models and students’ early ability towards the achievement of social studies for Accounting students class XII. This research uses an experimental approach with a 2 x 3 factorial design. Based on the result of data analysis, it can be concluded that there is a difference between using Group Investigations and Teams Games Tournament learning model towards students’ achievement by looking at the students’ early ability.Keyword : GI learning model, TGT learning model, students early ability.